The Impacts of Economic Sanctions on Supply Chain Management - Shakeri, Ehsan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Over the last two decades, supply chains have shown a great tendency of expanding their networks beyond the national boundaries and using the global sourcing strategy. As a result, supply chains have become more complex and dynamic networks that extend over several countries, including multiple tiers of suppliers, each of which may have various entities with different operations, structures and goals. In this situation, any uncertainty in the political and economic relations between countries should be considered as a source of risks. After the rise of unforeseeable political issues, one conceivable response of nations is imposing sanctions which lead to significant problems in seller-buyer relationships. This study has focused on the Iranian supply chains -which have been suffering from harsh economic and financial sanctions in the recent years- in order to investigate the impact of such sanctions on supply chain risk management (SCRM). After identifying the most significant supply chain risks associated with different flows, namely material, information and financial flows, the identified risks are analyzed via a qualitative method with respect to means of probability, impact and effect of sanctions. The impact of sanctions on different risk drivers, industries and supply chain performance measures are investigated. The results show that sanctions have the greatest negative impact on financial risks compared to the other risk drivers and all companies regardless of their industries and scopes are found to be vulnerable to sanctions. As to performance criteria however, the analyses disclose that supply chain cost and cash to cash cycle should receive more attention whenever the supply chain are influenced by sanctions. The analyses reveal that supply chain risk factors are really triggered by sanctions specifically risks of exchange rate movements, material price fluctuations, supplier bankruptcy, inability to collect all receivables and buying from a single source which should be viewed as the leading risk factor in the presence of sanctions. In the final stage, the high ranked risks are discussed and appropriate risk management strategies are proposed to deal with them. Keywords: Supply chain management, Sanctions, Risk management.

ÖZ: Son 20 yılda, tedarik zincirleri ulusal sınırların ötesinde kendi ağlarını genişleterek ve küresel tedarik stratejisi kullanarak büyük bir eğilim göstermiştir. Sonuç olarak, birden fazla katmanda her biri farklı işlemler, yapı ve hedefleri ile çeşitli varlıklara sahip olan tedarik zincirleri birçok ülkede yayılmış daha karmaşk ve dinamik ağlar haline gelmiştir. Bu durumda, ülkeler arasındaki siyasi ve ekonomik ilişkilerdeki herhangi bir belirsizlik risklerin kaynağı olarak kabul edilmelidir. Öngörülemeyen siyasi konuların artmasından sonra, ülkerin ilk tepkisi satıcı-alıcı ilişkilerinde sorunlar yol açacak yaptırımlarda bulunmatıv. Bu çalışma, son yıllarda sert ekonomik ve mali yaptırımlara uğramış, tedarik zinciri risk yönetimini fonksiyonların etkisini araştırmak için İran tedarik zincirlerine odaklanmıştır (SCRM). Farklı akışları ile en önemli tedarik zinciri risklerini tespit ettikten sonra, yani malzeme, bilgi ve finansal akımlar, belirlenen risklerin olasılık, çarpma ve yaptırımların etkisinin araçlarının açısından nitel yönteme analiz edilir. Farklı risk sürücüleri, sanayi ve tedarik zinciri performans önlemlerinin yaptırımların etkisi araştırılmıştır. Sonuçlar yaptırımlara bakılmaksızın sanayi ve kapsamların diğer risk sürücüleri ve tüm şirketlere kıyasla finansal yaptırımlara karşı savunmasız olarak kabul edilir olduğunu göstermektedir. Performans kriterleri açısından, tedarik zinciri yaptırımları zaman nakit döngüsündeki yaptırımlarda tedarik zinciri bundan etkilenmektedir. Analizler, özellikle döviz kurundaki hareketlerin riskleri tedarik zinciri risk faktörlerinin yaptırımlar tarafından tetiklendiğini ortaya koymaktadır, materyal fiyat dalgalanmaları, tedarikçi iflasi, tek bir kaynaktan satın almak için yetersiz tüm alacak toplama ve yaptırımlar lider risk faktörleri olarak görülmelidir. Son aşamada, yüksek sıradaki riskler tartışıldı ve bunlarla başa çıkabilmek için uygun risk yönetimi stratejileri önerılmıştır. Anahtar Kelimeler: Tedarik zinciri yönetimi, Cezai yaptırımlar, Risk yönetimi.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2016. Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Business logistics; Supply chain management; Sanctions; Risk management